Artificial uterus -research background to improve survival and outcome of extremely low birth weight newborns - Maria Laura Solerte (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
In clinical research, of worldwide interest, some medical devices are being studied as a new reproductive technology, which can both guarantee the implantation of the embryo or support the premature newborn outside the maternal uterus (human and animal); in focusing attention on the second aspect , exclusively, together with the ethical aspects widely debated by experts in the field, it is necessary to examine how much some researchers , belonging to many world groups, have created postnatal support mechanisms for animals extremely premature. On this ground, a group of experienced scientists are working now, using different technologies, to create an artificial womb, within the next decade, resembles the conditions in a human uterus more closely. Based on the fundamental concept, that every week of extra-uterine suitable care allows to get significant results for preterm newborn outcome and life, the " medical unit" will have to be studied and then implemented in details, to be used on human premature infants, even born at 22 weeks of gestation, who need specific assistance to ensure the development of severe immature fundamental organs and, therefore, normal cardiorespiratory functions, that are the cause of morbidity and mortality in these frail patients; the scientists will be develop a model destined for clinical use. Unlike current incubators, the prototypes will envelope the preterm babies in liquid and will provide them with oxygen and nutrition via an artificial placenta connected to newborns 's umbilical cord.